2008
DOI: 10.1002/bip.20958
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐helical peptides: An approach to collagen conformation, stability, and self‐association

Abstract: Peptides have been an integral part of the collagen triple‐helix structure story, and have continued to serve as useful models for biophysical studies and for establishing biologically important sequence‐structure‐function relationships. High resolution structures of triple‐helical peptides have confirmed the basic Ramachandran triple‐helix model and provided new insights into the hydration, hydrogen bonding, and sequence dependent helical parameters in collagen. The dependence of collagen triple‐helix stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 51 publications
3
132
1
Order By: Relevance
“…Perhaps ␣1(V)436 -447 fTHP might form small soluble aggregates that impede and complicate hydrolysis by MMP-12 but not the hydrolysis by gelatinases. Higher order self-association has been reported for some THPs (93). Alternatively MMP-12 might be more sensitive to product inhibition.…”
Section: ␣1(v) Thp Protection Of Mmp-12(e219a) Frommentioning
confidence: 89%
“…Perhaps ␣1(V)436 -447 fTHP might form small soluble aggregates that impede and complicate hydrolysis by MMP-12 but not the hydrolysis by gelatinases. Higher order self-association has been reported for some THPs (93). Alternatively MMP-12 might be more sensitive to product inhibition.…”
Section: ␣1(v) Thp Protection Of Mmp-12(e219a) Frommentioning
confidence: 89%
“…Similarly, a model for fibrous collagen with three left-handed polyproline type II (PPII) helices forming a right-handed supercoil was proposed (26) and then observed structurally (27). However, the formation of a unified hybrid structure composed of both α-and PPII helices was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 10% of native collagen sequences consist of the GPO triplet (42). Peptides containing GPO or GPP repeats also adopt a collagen-like triple helix (9). Using such model peptides, we showed that YadA binds as tightly to a hydroxyproline-rich collagenous triple helix as to native collagen (30).…”
mentioning
confidence: 97%